Cross-Border Knowledge Sharing in a Multinational Corporation: Case Deutsche Bank AG - Karkio, Heikki (My University, 2007)
It has been suggested that knowledge and intellectual capital go beyond organisations physical assets in creating competitive advantage. Multinational corporations are therefore able to create value through their ability to acquire knowledge from different locations and share it within their globally scattered network of units. In order to survive in the intensified global competition, multinational corporations need to recognize the strategic importance of cross-border knowledge sharing and to facilitate the context where it occurs in. The theoretical framework of the study builds on the theory of knowledge management. The study is divided into literature review and empirical research with the intention to describe various factors and issues that emerge from the multinational context and need to be considered in order to efficiently share knowledge across borders. The study is conducted as a qualitative case study by interviewing nine members of the case company located in five different countries on all major markets. The empirical research was able to point out that cross-border knowledge sharing in the case company takes place on three levels ranging from simple daily operative work to complex projects and initiatives that require deeper understanding and more experience. The different levels correlate with the complexity and increasing demand of requirements set on the different dimensions of knowledge sharing framework also presented in the study. In addition the characteristics emerging from the multinational context seem to exceed knowledge source and recipient specific factors in causing hindrance to the sharing process.
Keywords: knowledge management; knowledge sharing; multinational context; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|